A review on the existing visual tools for design students - Sheikh Abdul Aziz, Madihah; Lindgaard, Gitte; Hamzah, Mohd Syarqawy; Whitfield, T.W. Allan (Indian Journal of Science and Technology, 2017)
This paper explores possible solutions to overcome the problem of design students lacking the skills and knowledge of user testing and data analysis to inform design decision-making that can help them to create successful products. A preliminary investigation and review is reported of existing visual interactive software tools intended to support design students and lecturers. Some of these tools might meet the requirements for teaching sampling methods (selecting suitable people and products) as well as testing techniques including data collection, analysis, and interpretation to design students. A discussion of existing visual software tools is presented first, followed by a dis-